Family support and medication adherence as determinants of patient decision-making in heart failure symptom management - Rahmadani, Hanifa Eka; Kristinawati, Beti (Institute of Computer Science (IOCS), 2025)
Heart failure patients frequently experience difficulties in making decisions related to symptom management. This study aims to determine the relationship between family support and medication management behavior with heart failure patients’ decision-making in managing clinical symptoms. This study uses a quantitative approach with a cross-sectional design and involves 270 heart failure patients at a regional hospital in Central Java in 2025. The instruments used include the Family Support Scale (FSS) questionnaire, the Adherence to Refill Medication Scale (ARMS), and the Decisional Conflict Scale (DCS). The research findings indicate that the majority of respondents received good family support (69.3%), exhibited high medication management behavior (52.6%), and were confident in making decisions regarding symptom management (89.3%). Statistical analysis showed a significant positive correlation between family support and decision-making (ρ = 0.595; p = 0.000), as well as between medication management behavior and decision-making (ρ = 0.126; p = 0.039). Family support and medication management behavior have a significant positive relationship with patients' confidence in making decisions regarding the management of their clinical symptoms. It is recommended to strengthen family support and improve medication management behavior to make it easier for patients to make decisions regarding the management of their disease symptoms. Healthcare professionals should involve family members in patient education and self-care programs, while hospital policymakers can develop family-based interventions to enhance patients’ decision-making confidence.